Emergency smartwatch for fisherman - Hamidou, Saoud; Abdoul-Halim, Mohamed Abdallah; Abdulghafor, Rawad Abdulkhaleq Abdulmolla; Wani, Sharyar (International Journal on Perceptive and Cognitive Computing (IJPCC), 2020)
This work is about designing a smartwatch that is used mostly by fishermen. The watch provides the location of the user using the global positioning system (GPS) and a panic button that he can use in case of emergency. It can record the heart rate by using a heart rate sensor. The paper works with a software that is used by the appropriate authorities; they record the information provided by the smartwatch. The third part of the paper is a mobile application used by the rescue team; the application shows the location of the fisherman. This paper aims to help fishermen in case of emergency cases, they can be saved by the rescue team. Based on the heart rate sensor and the panic button provided by the smartwatch, the appropriate authorities can know when a fisherman needs help and send the rescue team.